Progesterone receptor membrane component 1 and its role in ovarian follicle growth - Peluso, John J. (Frontiers in Neuroscience, 2013)
Progesterone (P4) is synthesized in the ovary and acts directly on granulosa cells of developing ovarian follicles to suppress their rate of mitosis and apoptosis. Granulosa cells do not express nuclear progesterone receptor (PGR) but rather progesterone receptor membrane component-1 (PGRMC1). PGRMC1 binds P4 and mediates P4’s actions, as evidenced by PGRMC1 siRNA studies. PGRMC1 acts by binding plasminogen activator inhibitor 1 RNA binding protein and regulating gene expression. Specifically, PGRMC1 suppresses some genes that promote cell death (i.e. Bad, Caspase-3, Caspase-4). P4 regulates gene expression in part by inhibiting PGRMC1 binding to Tcf/Lef transcription sites, thereby reducing Tcf/Lef transcriptional activity. Since Tcf/Lef transcription sites are located within the promoters of genes that initiate mitosis and/or apoptosis (i.e. c-jun and c-myc), P4-PGRMC1 mediated suppression of these Tcf/Lef regulated genes could account for P4’s actions. PGRMC1 expression is also altered in women with polycystic ovarian syndrome, premature ovarian failure and infertility. Collectively, these observations support a role for PGRMC1 in regulating human ovarian follicle development.